Afbrydelsesstrategier: Om afbrydelsen som begivenhed og iscenesættelsesstrategi i en performativ æstetik - Christoffersen, Erik Exe (Peripeti, 2021)
The article discusses interruption as an artform, as a strategy and as traditions of discontinuity in theatre and performance art. The interruption creates a form of error in the work of art and in different media. This means that performative forms can be seen as projects of autenticity. Finaly the article claims that the interruption in work of art is a part of the eventness of the performance.